Harnessing Insect Toxins: Advancements in Medicine and Biotechnology - Sughra Yasin; Hifza Waris; Alia Akram; Misbah Nazir; Iqra Waris; Iqra Tariq (Dialogue Social Science Review (DSSR), 2025)
The application of insect toxins in the fields of medicine and biotechnology has emerged as a highly promising avenue for advancing therapeutic approaches. Derived from various venomous arthropods and insects, these toxins comprise a diverse array of bioactive compounds distinguished by unique structural and functional properties. This comprehensive review investigates recent progress in leveraging insect toxins for medical purposes, emphasizing their roles in pain management, cancer therapy, immunomodulation, and antimicrobial activities. Furthermore, it explores the escalating significance of insect toxins in biotechnology, serving as research tools and contributing to areas such as tissue engineering, regenerative medicine, and drug delivery systems. The review also addresses the potential of insect toxins in precision medicine and eco-friendly pest control strategies. As scientific research continues to evolve, the ongoing exploration of novel applications of insect toxins holds considerable promise for advancing both human health and biotechnological innovations.